Optimal pathological response after neoadjuvant chemotherapy for muscle‐invasive bladder cancer: results from a global, multicentre collaboration. (18th May 2021) - Ravi, Praful; Pond, Gregory R.; Diamantopoulos, Leonidas N.; Su, Christopher; Alva, Ajjai; Jain, Rohit K.; Skelton, William P.; Gupta, Sumati; Tward, Jonathan D.; Olson, Kathleen M.; Singh, Parminder; Grunewald, Camilla M.; et al.
Abstract : Objectives: To evaluate outcomes of patients achieving a post‐treatment pathological stage of <ypT2N0 at radical cystectomy (RC) following neoadjuvant chemotherapy (NAC) for muscle‐invasive bladder cancer (MIBC) to identify an optimal definition of pathological response. Patients and Methods: Patients from 10 international centres who underwent NAC for cT2–4aN0–1 MIBC and achieved <ypT2N0 disease at RC were included. The primary outcome was time to recurrence, either local or distant. Kaplan–Meier and Cox proportional hazards regression were used to evaluate associations between clinicopathological variables and outcomes. Results: A total of 625 patients were included. The median age was 66 years and 80% were male. Gemcitabine and cisplatin (GC, 56%) and methotrexate, vinblastine, doxorubicin and cisplatin (MVAC)/dose‐dense (dd)MVAC (32%) were the most common NAC regimens. ypT0, pure ypTis, ypTa ±ypTis and ypT1 ± ypTis were attained in 58.1%, 20.0%, 7.6% and 14.2% of patients, respectively. The cumulative incidence of recurrence at 5 years was 9%, 16%, 29% and 30%, respectively. Pathological stage was prognostic for recurrence, with ypTa ± Tis (hazard ratio [HR] 3.20, 95% confidence interval [CI] 1.40–7.30) and ypT1 ± Tis disease (HR 4.03, 95% CI 2.13–7.63) associated with a significantly higher recurrence risk. Pure ypTis (HR 1.66, 95% CI 0.82–3.38) and the type of NAC regimen (ddMVAC: HR 1.59, 95% CI 0.55–4.56; MVAC: HR 1.18, 9%% CI 0.25–5.54; reference: GC) were not associated with recurrence. Conclusion: We propose that optimal pathological response after NAC be defined as attainment of ypT0N0/ypTisN0 at RC. Patients with ypTaN0 or ypT1N0 disease (with or without Tis) at RC displayed a significantly higher risk of recurrence and may be candidates for trials investigating adjuvant therapy.